Children hospitalised with influenza‐associated pneumonia during the 2009 pandemic displayed increased disease severity. (30th January 2015) - Tasher, Diana; Stein, Michal; Solomon, Clara; Shachor‐Meyouhas, Yael; Glikman, Daniel; Mandelboim, Michal; Kassis, Imad; Somekh, Eli
Abstract Aim The precise role of the influenza virus in the morbidity of hospitalised paediatric pneumonia cases is unknown. We identified how many cases hospitalised during the 2009 pandemic had influenza‐associated pneumonia and assessed their severity. Methods Children admitted to three Israeli medical centres during the 2009 influenza pandemic with radiologically confirmed pneumonia were prospectively screened for influenza. We compared the clinical, laboratory and radiologic findings for positive and negative cases. Results The pandemic H1N1 virus was detected in 89 (30%) of the 297 patients hospitalised for pneumonia and 55% of the Paediatric Intensive Care Unit admissions for pneumonia. There were no significant differences in the rates of underlying disease between the two groups. Logistic regression analysis revealed that children with pandemic H1N1 virus‐associated pneumonia had significantly increased disease severity than those without, with a higher incidence of hypoxemia (41.6% versus 24%) with a relative risk (RR) of 2.2, higher rate of paediatric intensive care unit admission (16.9% versus 5.8%, RR of 2.7) and higher rate of mechanical ventilation (10.1% versus 2.4%, RR:4.4). Conclusion During the 2009 influenza pandemic, 30% of children hospitalised for pneumonia had the influenza infection and these children displayed increased disease severity.